The Expression of AGO2 and DGCR8 in Idiopathic Sudden Sensorineural Hearing Loss - Soon Yong Han; Shin Kim; Dong-Hoon Shin; Jae Hyun Cho; Sung-Il Nam (Clinical and Experimental Otorhinolaryngology, 2014)
ObjectivesThe microRNAs have been implicated in the development and function of the inner ear, especially in contribution to hearing. However, the impact of idiopathic sudden sensorineural hearing loss (SSNHL) on expression of miRNA biogenesis-related components has not been established. To investigate the regulations of microRNA (miRNA) biogenesis-related components, argonaute 2 (AGO2) and DiGeorge syndrome critical region gene 8 (DGCR8) mRNA expression in SSNHL and to evaluate the value of clinical parameters on their expression.MethodsThirty-seven patients diagnosed with SSNHL and fifty-one healthy volunteers were included in this study. We measured mRNA expression levels of AGO2 and DGCR8 in whole blood cells but erythrocytes of patients with SSNHL and controls, using reverse transcription and real-time polymerase chain reaction analysis.ResultsThe mRNA expression level of AGO2 is upregulated in SSNHL. The expression level of AGO2 was significantly correlated with that of DGCR8 in both patients with SSNHL and controls. Expression level of AGO2 in SSNHL was correlated with white blood cell counts.ConclusionThis study demonstrated for the first time that the AGO2 mRNA expression level was upregulated in SSNHL, suggesting its important role in pathobiology of SSNHL development.